Label-free bacterial detection using polydiacetylene liposomes. Issue 68 (19th July 2016) - Park, Jimin; Ku, Seul Kathy; Seo, Deokwon; Hur, Kahyun; Jeon, Hojeong; Shvartsman, Dmitry; Seok, Hyun-Kwang; Mooney, David J.; Lee, Kangwon
Abstract : Label-free bacterial sensors using specific interplay between released-surfactin and polydiacetylene (PDA) liposomes. Abstract : Polydiacetylene (PDA) liposomes were prepared to selectively capture target released from bacteria. Specific interplay between released-surfactin and PDA resulted in a conformal change in the structure of PDA, highlighting the potential of indirect interactions between bacteria and PDA in the construction of new label-free bacterial sensors.